1999
DOI: 10.1002/(sici)1521-3773(19990201)38:3<386::aid-anie386>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of C−O by P−O in Cyclic Acetals and Ketals

Abstract: Efficiency and structural specificity earmark the reaction of phosphonium ions 1 with cyclic acetals and ketals to yield 1,3,2-dioxaphospholanium ions 2 [Eq. (1)]. Potential applications of this reaction are in monitoring trace levels of organophosphorus esters and in developing novel carbonyl deprotection agents. R=OCH , CH ; R =H, CH ; R =CH , C H ; R =H, CH .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…This reaction is analogous to reactions of acylium ions RCO ϩ and cyclic acetals or ketals like 1,3-dioxolane (eq 2 in Scheme 1) by the gas-phase transacetalization mechanism initially discovered by Eberlin et al [22][23][24][25][26]. In Eberlin reactions, structures of product ions have been clearly determined by their fragmentation patterns [21,22] and by isotopelabeling experiments [27] and transacetalization mechanisms are well established. Not only have the reactions been studied extensively but these reactions have already found analytical and synthetic applications [28 -32].…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…This reaction is analogous to reactions of acylium ions RCO ϩ and cyclic acetals or ketals like 1,3-dioxolane (eq 2 in Scheme 1) by the gas-phase transacetalization mechanism initially discovered by Eberlin et al [22][23][24][25][26]. In Eberlin reactions, structures of product ions have been clearly determined by their fragmentation patterns [21,22] and by isotopelabeling experiments [27] and transacetalization mechanisms are well established. Not only have the reactions been studied extensively but these reactions have already found analytical and synthetic applications [28 -32].…”
mentioning
confidence: 78%
“…An earlier study from this laboratory reported the formation of cyclic 1,3,2-dioxaphospholanium ions in the ketalization reactions of phosphonium ions CH 3 P(O)OCH 3 ϩ (93 Th) and CH 3 OP(O)OCH 3 ϩ (109 Th) with 1,3-dioxolane (eq 1 in Scheme 1) [21]. The ketalization reaction involved transacetalization in which the protecting group of 1,3-dioxolane, the oxirane CH 2 CH 2 O moiety, was transferred onto the phosphoryl group, producing the cyclic 1,3,2-dioxaphospholanium ion and releasing the free ketone.…”
mentioning
confidence: 99%
“…Benzomorpholine, 3,4-dihydro-2H-1,4-benzoxazine, is a constituent of many naturally occurring substances [46]. An earlier study [51] from this laboratory reported that arenesulfenylium cation PhS ϩ can undergo the Eberlin reaction with 2,2-dimethyl-1,3-dioxolane, a cyclic ketal and form a characteristic four-membered cyclic product, 2-aryl-1,2-oxathietan-2-ium ion (the prototype Eberlin reaction [52][53][54][55] is the gas-phase transacetalization of acylium ions RCO ϩ by cyclic acetals or ketals, as shown in Scheme 7). It is therefore important to seek new simple routes for the synthesis of benzomorpholine.…”
Section: Synthesis Of N-heterocycles Using Arylnitrenium Ionsmentioning
confidence: 99%
“…This reaction led to an adduct ion [RR′CHCOOR″, OP(OCH 3 ) 2 ] + which loses spontaneously a molecule of ketene (CH 2 CO) or substituted ketene (RR′CCO) 19. Cooks and co‐workers found that phosphonium ions undergo structurally diagnostic transacetylation with 1,3‐dioxolane20a and 1,4‐dioxane20b to generate 1,3,2‐dioxaphospholanium ions.…”
Section: Introductionmentioning
confidence: 99%